Effectivity of Mengkudu (Morinda citrifolia) Fruit Extract in Inhibiting the Growth of Streptococcus viridans Causing Dry Socket Post Extraction - Dohude, Gostry Aldica; -, Ahyar Riza; Siregar, Indra Basar; -, Ayu Lestari (Dentistry Faculty, 2024)
Background: Post-extraction wound healing usually proceeds but sometimes has problems and causes complications in the form of a dry socket. Streptococcus viridans bacterial infection is one of the causes of dry socket, therefore prevention of infection can be done by providing antibiotic or antibacterial (antiseptic) therapy. Noni fruit (Morinda citrifolia) contains many phenols, saponins, and alkaloids that can potentially be antibacterials. Objective: This study aims to determine the effectiveness of noni (Morinda citrifolia) extract against Streptococcus viridans bacteria in post-extraction sockets. Methods: This type of research is a laboratory experiment with Post test only control group design, where this study uses the Kirby-Bauer diffusion method with Streptococcus viridans bacteria samples and uses noni fruit extract (Morinda citrifolia) with concentrations of 3.125%, 6.25%, 12.5%, 25%, and 50%; Positive control Chlorhexidine digluconate 0.2%; And negative control DMSO. Results: The data analysis using Kruskal-Wallis showed a p-value of 0.000 on inhibition, which showed that noni fruit extract could inhibit the growth of Streptococcus viridans bacteria. Conclusion: Noni fruit extract (Morinda citrifolia) effectively inhibits the growth of Streptococcus viridans bacteria with an effective dose of 50%, but the antibacterial activity is still below the activity of Chlorhexidine gluconate 0.2%.